Employee Acceptance Decision Support System Using The Smart Method (Case Study on Association of The Indonesian Electrical and Mechanical Contractors Samarinda City) - Aldy Septian Derry; Bartholomius Harpad; Yunita Yunita (TEPIAN, 2021)
Decision Support System (DSS) is a system that can assist someone in making accurate and targeted decisions. Many problems can be aasolved by using SPK, one of which is the acceptance of employees at the Gaklimdo Samarinda Association using the SMART (Simple Multi Attribute Rating Technique) method. The purpose of this research is to produce a Decision Support System for Employee Admission Using the SMART Method (Case Study of the Gaklimdo Association of Samarinda City) with the hope that the selection of employees will be carried out objectively. By using the PHP programming language and the database used is MySql. In this study, the data collection techniques used were literature study, observation and interviews. The result of this research is the creation of a decision support system to make employee decisions that are accepted, and not accepted as employees. Users can input prospective employee data, criteria data and sub-criteria data. Then the system will look for a solution using the SMART (Simple Multi Attribute Rating Technique) method. After the decision is obtained, the system will display the decision.